Presence of Cognitive Deterioration and Anatomical-Clinical Topography in Patients with Epilepsy in Cienfuegos - Rolando Lázaro Rivera López; Aleima Rodríguez Carvajal; Ricardo Verdecia Fraga (Revista Finlay)
Background: epilepsy is a pathological condition characterized by a recurrent non-provoked crisis, however, the presence of the crisis is a fraction of the global problem, patients with epilepsy develop a variety of neuropsychiatry problems, as cognitive affection, most of all, in the space of memory. Objective: evaluating the behavior of the cognitive deterioration and focalization according to anatomical- clinical topography in patients with epilepsy. Methods: a descriptive, correlational, cross-section and follow-up study of cases. The techniques used were: structured interview, the Montreal Cognitive Assessment's evaluation, and Luria´s neuropsychological exam. It was used SPDD statical parcel, version 1.5 to process the information that made possible the study of the obtained data, with the aim of expressing the results in chart of frequency and relation of variables in number and percent. Results: the 71.4 % of evaluated patients presented cognitive deterioration in any of its of measurement scales and they focalized according to neuropsychological exam. Conclusions: as the time of evolution of the disease increases, the frequency and duration of the crises, the grade of the cognitive deterioration in patients with epilepsy increases, focalizing with dysfunction majority fronto-temporary level according to anatomical-clinical topography.